High throughput optimization of protein-A affinity chromatography for capture of humanized monoclonal antibody - Pakiman, Norazrina (2012)
Monoclonal antibody (mAb) is a specific protein molecule that is widely used in biopharmaceutical industry for therapeutic and diagnostic application. The purification of the mAb products typically involved Protein-A affinity chromatography as the first capture step driven by the very specific binding of the mAb to Protein-A ligand. Optimization of the Protein-A affinity step is required to improve the performance and economics of the purification step, particularly to improve binding capacity, recovery of the product and to minimize formation of product aggregates. A typical approach for performing chromatography optimization in column operation is somehow time consuming and require significant amount of mAb sample. In this study, a high-throughput chromatography operation in 96-well filter plate was explored to perform the chromatography optimization. Conditions for binding and elution were optimized by looking at different combination of pH and salt concentration for binding and different buffer type, concentration and pH for elution. Based on Design of Experiment (DOE) analysis, a 20 mM sodium phosphate buffer with addition of 180 mM sodium chloride at pH 7.4 was selected based on optimum binding. For elution, a 100 mM Glycine buffer at pH 3.2 was optimized in order to maximize recovery and minimizing formation of aggregates. Evaluation of binding capacity under static condition in the 96-well filter plate and dynamic binding in column operation were also performed. The maximum equilibrium capacity was determined at 59.6 mg IgG/ml resin while the 10% breakthrough capacity was observed at 53.3 mg IgG/ml resin and 46.4 mg IgG/ml resin at 150 cm/hr and 300 cm/hr flow rate respectively. The loading capacity was then calculated and a case study for purification of 100 L mAb sample was performed to evaluate the volumetric production rate at different flow rate. Based on the case study, flow rate of 300 cm/hr with 35 mg IgG/ml resin loading capacity was selected. Verification runs at the optimized conditions were performed in plate and column chromatography approach, and the performance of the purification was compared. Based on the results, the average recovery was achieved at 96.63 ±2.58% with an average aggregation index of 5.29 ±0.42. These results are very much comparable with the predicted data from DOE analysis. The impurities profile of the runs was also assessed where the results shows comparable profile for both product purified in column and plate chromatography operation.